2011
DOI: 10.3109/02699206.2011.602460
|View full text |Cite
|
Sign up to set email alerts
|

Electropalatographic specification of Croatian fricatives /s/ and /z/

Abstract: Electropalatographic specification of alveolar fricatives in Croatian is aimed at providing speech therapists with normative data about the range of acceptable productions of /s/ and /z/ in adult speakers of Croatian. Four variables were analysed: place of articulation, total contact, groove width and hold phase duration. Intra- and inter-speaker variability for each variable was analysed. Lingual palatal cues for voicing difference were also quantified and discussed. Results show that Croatian /s/ and /z/ are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
1
12
0
2
Order By: Relevance
“…Speech material used in this study was extracted from the simultaneous EPG and acoustic corpus of Croatian speech (CROELCO). A detailed description of the CROELCO corpus was presented in Liker (2009) and Liker, Horga & Mildner (2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech material used in this study was extracted from the simultaneous EPG and acoustic corpus of Croatian speech (CROELCO). A detailed description of the CROELCO corpus was presented in Liker (2009) and Liker, Horga & Mildner (2012).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the CROELCO corpus was presented in Liker (2009) andLiker, Horga andMildner (2012).…”
Section: Speech Materialsmentioning
confidence: 99%
“…Voiced consonants are often described as less resistant to coarticulation than their voiceless counterparts, which is explained by lower tongue-to-palate contact in voiced tokens (Recasens, 1999). However, many EPG studies showed that voiced fricatives had increased tongue-to-palate contact and a smaller groove than voiceless fricatives (Dagenais et al, 1994;Dixit and Hoffman, 2004;Liker and Gibbon, 2011;Liker et al, 2012), although this issue can be related to the position in the syllable . The finding that voiceless fricatives showed lower tongue-to-palate contact and a wider groove than their voiced counterparts was mostly explained by aerodynamic factors, whereby the air pressure during voiceless fricatives was so high that it pushed out the lateral edges of the tongue, thus creating a wider groove and less tongue-to-palate contact in the voiceless than in the voiced fricative.…”
Section: Fig 12mentioning
confidence: 99%
“…Acoustic and articulatory characteristics of voicing differ from one language to another (Browman and Goldstein, 1986;Dagenais et al, 1994;Docherty, 1992;Fuchs, 2005;Fuchs et al, 2007;Gordeeva and Scobbie, 2007;Liker et al, 2012;Pinho et al, 2012). For example, in languages like English or German it is common for phonologically voiced obstruents to be partially or completely voiceless phonetically, while in languages like Czech or Croatian this process is much less common (Bakran, 1996;Skarnitzl et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation